Social Capital as a Community Strategy for Coping with Economic Uncertainty - Ika Rahma (Archipel: Journal of Indonesian Interdisciplinary Studies, 2026)
Economic uncertainty has become a persistent challenge affecting communities, institutions, and households across various contexts. In response, social capital—comprising networks, trust, and shared norms—has emerged as a critical resource for enhancing resilience and supporting adaptive economic strategies. This study aims to analyze the role of social capital in addressing economic uncertainty by examining its forms, functions, and contributions to coping mechanisms and community resilience. This research employs a qualitative approach with a descriptive-analytical design, utilizing a library research method. Data were collected through document analysis of scholarly articles and analyzed using an interactive model involving data reduction, data display, and conclusion verification, supported by thematic coding and triangulation techniques. The findings reveal that social capital operates across multiple levels, including communal networks, trust-based relationships, business collaborations, and household interactions. These forms of social capital facilitate risk-sharing, resource access, flexibility, and innovation, thereby strengthening economic resilience. The discussion highlights that social capital functions as both a coping mechanism and a strategic asset, enabling communities to adapt to economic disruptions more effectively. In conclusion, social capital plays a vital role in mitigating economic uncertainty, but its effectiveness depends on the integration of local practices, institutional support, and adaptive capacity to sustain long-term resilience.